Pengaruh Keberadaan Bumdes Terhadap Pendapatan Usaha Warung Sembako Di Desa Harapan Makmur Selatan Kecamatan Bagan Sinembah Raya Kabupaten Rokan Hilir Provinsi Riau - Susanti Susanti; Julienda Br Harahap; Nilawati Nasti (Universitas Islam Sumatera Utara, 2022)
The existence of Village-Owned Enterprises (BUMDes) as Strengthening the Village Economy. This village-owned enterprise is one of the institutions engaged in the social and economic fields and as a service provider to the village community, especially regarding the business sector. The research method used in this study is a qualitative research with a descriptive approach, with a focus on research: inequality between BUMDes and the food stall business. The results of this study are that the existence of village-owned enterprises is in accordance with the regulations regulated by the village with village regulations regarding village-owned enterprises, but there is a significant effect on the income of the food stall business.It is known that the t-count before and after the existence of BUMDes is 4.706 with prob (0.000 0.05). Thus, the results obtained are Ho is rejected which explains that there is a difference before and after the existence of BUMDes which is calculated based on the income of the food stall business before and after the BUMDes, meaning that BUMDes has an effect on the decrease in the income of the basic food stall business.